Az én poézisom: Fazekas Mihály költészetének líratörténeti helyéről - Vaderna, Gábor (Studia Litteraria, 2020)
Mihály Fazekas’s poetry is often associated with the discourses of popular culture. His descriptive poems on nature, his songs and elegies describing the everyday life of the military, and his narrative poem, Lúdas Matyi, which is considered to be a classic in Hungarian literature, have all been interpreted as reaching back to the original culture of the Hungarian nation. This description was mainly based on Herder’s concept of nation and history. However, Fazekas was not interested at all in the problem of recovering a pure Volksgeist from folk culture. This essay argues that the fundamental aesthetic problem of his poetry is creating poetry of social life. For Fazekas, folk culture is not a cultural entity to be uplifted or an entity to be adapted, but an important register of cultural diversity. Poetry is nothing more than a means of making culture social. thus, poetry achieves its goal if the different poetical registers reach different social classes.